Exploring the extreme Universe with the Fermi Large Area Telescope - Menezes, Raniere Maciel de (2020)
High-energy astrophysical processes commonly happen in the surroundings of compact objects, like neutron stars and black holes. In such environments, relativistic particles can emit gamma-rays and also scatter low-energy photons up to the gamma-ray domain. With the launch of the Fermi Large Area Telescope (LAT) in 2008, a new window was open to the gamma-ray sky, allowing us to observe a huge variety of astrophysical phenomena never seen before. Fermi-LAT\'s remarkable sensitivity in the 100 MeV - 500 GeV energy band allowed for the detection of more than 5000 gamma-ray sources and this number is still growing. In this thesis, we use the unprecedented Fermi-LAT capabilities in two different ways. In the first half of the thesis, we explore the gamma-ray emission from globular clusters and low-luminosity active galactic nuclei (LLAGNs), where both classes are poorly understood in the high-energy domain. By using roughly 10 years of gamma-ray observations, we are able to uncover some aspects of the dynamical formation of millisecond pulsars (MSPs) in globular clusters, especially on how stellar close encounters in the cores of globular clusters can form and/or disrupt compact mass-transferring binary systems, which could potentially evolve into gamma-ray emitting MSPs. With a similar analysis, we explore the mechanisms behind the gamma-ray emission of LLAGNs, this time also comparing hadronic and leptonic models for high-energy processes happening in the black hole surrounding hot accretion flow. In the second half of the thesis, we use Fermi-LAT data to associate gamma-ray sources with their optical-infrared counterparts. Although the Fermi-LAT spatial resolution, typically <5\', is the highest ever achieved for a gamma-ray space-based telescope, it is not enough to avoid problems with source association. In fact, 25% of the gamma-ray sources listed in the last Fermi-LAT catalog have no obvious low-energy counterpart. To face this problem, we work on three distinct, direct and indirect, counterpart identification methods. At first, we use the correlations between mid-infrared colors and gamma-ray emission to better select and characterize the counterpart candidates of Fermi-LAT blazars. We then develop an alternative method of counterpart association by accounting for the mid-infrared colors and radio loudness when computing the association probability with the likelihood ratio method. Finally, we perform a direct search for counterparts by doing an optical spectroscopic follow up of a few tens of sources. The results from these approaches are very promising, especially on the association and selection of future targets for spectroscopic follow up of Fermi-LAT blazars.